HABITUATING METHOD: BUILDING EARLY CHILDHOODS’ DISCIPLINE CHARACTER - Rina Rosdiana; Idah Haidah; Alberthina Abetsi Haumahu (Jurnal Intisabi, 2026)
One of the efforts to form a quality generation is to instill religious and moral values in children from an early age. This study aims to identify the application of habituation of religious and moral values, as well as the positive impact of the application of habituation of religious and moral values in strengthening discipline attitudes in children aged 5-6 years at the Al-Khoeriyah early childhood education. The method used in this study is class action research (CAR). The results of this study show that the the implementation of learning religious and moral values through the habituation method in early childhood is included in the category of good. This is based on an enhancement of the score 56.5% in pre-cycle, then become 69.8% in cycle I, and become 84.8% in cycle II. This significant enhancement directly has a positive impact on four main behaviors: (1) the children can worship better, (2) the children behave honestly and politely, (3) the children maintain personal and environmental cleanliness, and (4) the children know religious values in daily life. In conclusion, the implementation of habituation method has a positive impact on applying religious and moral values to children aged 5-6 years at the Al-Khoeriyah early childhood education.